2009
DOI: 10.1007/s00264-009-0801-6
|View full text |Cite
|
Sign up to set email alerts
|

Patients with fixed flexion deformity after total knee arthroplasty do just as well as those without: ten-year prospective data

Abstract: Range of motion (ROM) is an important outcome variable after total knee arthroplasty (TKA). This may be compounded by a pre-existing fixed flexion deformity (FFD). We therefore examined the long-term outcomes of patients with a flexion deformity undergoing TKA compared to those without a preoperative fixed flexion deformity. Participants who had undergone TKA at our centre between 1989 and 2002 were examined preoperatively, one, five and ten years after TKA (Kinemax PS; Howmedica, Rutherford, NJ, USA). Examini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Nexgen LPS-Flex 35 (35) 104 (17) 106 (14) N/S N/S Nutton et al [13] 2008 Scotland In the selected papers, the method of measurement of ROM was generally unclear and lacked uniformity. Ten of the studies indicated their means of measurement using a universal goniometer [12-14, 16, 26-28, 30, 34, 35, 38] and only six reported basic technical details [13,14,16,26,28,33]. There were only four studies that reported a randomised controlled trial (RCT) comparing H-F PS and conventional PS TKAs [11,13,15,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nexgen LPS-Flex 35 (35) 104 (17) 106 (14) N/S N/S Nutton et al [13] 2008 Scotland In the selected papers, the method of measurement of ROM was generally unclear and lacked uniformity. Ten of the studies indicated their means of measurement using a universal goniometer [12-14, 16, 26-28, 30, 34, 35, 38] and only six reported basic technical details [13,14,16,26,28,33]. There were only four studies that reported a randomised controlled trial (RCT) comparing H-F PS and conventional PS TKAs [11,13,15,20].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, four dealt with the comparison of PS TKA and cruciate retaining (CR) TKA [30,31,33,35]; two were the comparison of PS TKA with PS mobile-bearing TKA [27,36]; one was the comparison of PS TKA to H-F PS mobile-bearing TKA [32]; and one was the comparison of PS TKA with H-F PS TKA [13]. Six of the 18 selected studies were case controlled studies that included the H-F PS TKAs [12,14,16,28,29,37]. Among these, four dealt with comparison of standard PS TKA to H-F PS TKA [12,14,16,29]; one study was on the comparison of flexion contracture patients to the no-flexion contracture patients [28] and one study was on the comparison of MIS PS TKA to conventional TKA [37].…”
Section: Literature Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the fact that the fixed-bearing group had a statistically significantly greater preoperative mean flexion deformity. It has recently been shown by Cheng et al [25] that subjects with a pre-existing fixed flexion deformity had a statistically significantly greater improvement in extension than subjects without, due to operative correction of the deformity.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have reported that the condition does not improve postoperatively [17][18][19][20], other investigators have shown gradual recovery with conservative management [19,[21][22][23][24]. It has been well established that the presence of a preoperative flexion contracture increases the risk of developing a postoperative flexion contracture [5].…”
Section: Discussionmentioning
confidence: 99%